FLUKTUASI NILAI TUKAR RUPIAH & DAMPAKNYA TERHADAP IMPOR KEDELAI DARI AMERIKA SERIKAT KE INDONESIA PERIODE 2018 - 2024 - Ratu Aribah Santika Xaviera; Aisyah Fahriza Anindita; Alfina Marta; Aradea Margareta; Rara Marcella; Ahmad Setiawan Nuraya (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This study aims to analyze the relationship between fluctuations in the rupiah exchange rate and the volume of soybean imports from the United States to Indonesia during the period 2018-2024. The data used includes the average exchange rate of the rupiah against the US dollar per year, the volume of soybean imports per year, as well as relevant macroeconomic factors such as global soybean prices, government import policies, and domestic demand. The analysis shows that the rupiah exchange rate experienced significant fluctuations during the period, especially in 2020 due to the COVID-19 pandemic and in 2022 due to global economic instability. These fluctuations significantly affected the volume of soybean imports, where a weakening exchange rate tends to decrease the volume of imports due to increased import costs in rupiah terms. Descriptive statistics show that there is a negative correlation between the exchange rate and import volume, which is confirmed through linear regression analysis. The regression results show that the rupiah exchange rate has a significant effect on the volume of soybean imports from the United States. In addition, other variables such as world soybean prices, subsidy and import duty policies, and demand from the domestic industry also influence fluctuations in import volume. Thus, the stability of the rupiah exchange rate is a key factor in maintaining a smooth and adequate supply of imported soybeans, which is very important for the national food industry.